2013
DOI: 10.1186/1476-4598-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with ABT-737 and chloroquine in preclinical models of small cell lung cancer

Abstract: BackgroundNew therapies are urgently needed for patients with small cell lung cancer (SCLC). Chemotherapy and targeted therapies, including the Bcl-2 inhibitor ABT-737, may induce tumor cell autophagy. Autophagy can promote survival of cancer cells under stress and comprise a pathway of escape from cytotoxic therapies.MethodsWe explored the combination of ABT-737 and chloroquine, an inhibitor of autophagy, in preclinical models of SCLC. These included cell culture analyses of viability and of autophagic and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…13 In contrast, in a recent study where hydroxychloroquine was administered at a dose of 162 mg/kg, approximately equivalent to a human dose of 800 mg, tumor growth delay induced by erlotinib is markedly increased in the H358 lung cancer cell line. Interestingly, even at a dose that is relatively high compared with most other published in vivo work, chloroquine demonstrates only minimal extension of tumor growth delay in the H460 tumor cell line 14 despite the fact that chloroquine is equally effective in sensitization of these two cell lines in culture.…”
mentioning
confidence: 82%
“…13 In contrast, in a recent study where hydroxychloroquine was administered at a dose of 162 mg/kg, approximately equivalent to a human dose of 800 mg, tumor growth delay induced by erlotinib is markedly increased in the H358 lung cancer cell line. Interestingly, even at a dose that is relatively high compared with most other published in vivo work, chloroquine demonstrates only minimal extension of tumor growth delay in the H460 tumor cell line 14 despite the fact that chloroquine is equally effective in sensitization of these two cell lines in culture.…”
mentioning
confidence: 82%
“…Acta Pharmacologica Sinica npg growth factor receptor (EGFR) [22] , and of ABT-737, the Bcl-2 inhibitor [23] . Our results showed that LDM and CQ individually reduced tumor growth in vitro and in vivo.…”
Section: Wwwchinapharcom Liu F Et Almentioning
confidence: 99%
“…17 In contrast to apoptosis, autophagy is generally a cytoprotective mechanism that maintains intracellular homeostasis by removing harmful mal-folded proteins, protein aggregates, and damaged organelles, 18 whereas autophagy inhibition promotes BH3-mimetic lethality. 19 Importantly, a recent study demonstrated that Bim inhibits autophagy by sequestering Beclin-1 at microtubules. 20 Conversely, histone deacetylase inhibitors (HDACIs) upregulate Bim in tumor cells, including MM cells.…”
Section: Introductionmentioning
confidence: 99%